(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
Based on 69 specimens, using morphometric, meristic and osteological characters, we describe a new species of Hemibrycon from the Rancheria River, a Caribbean coastal drainage of eastern Colombia that drains the Sierra Nevada de Santa Marta. H. santamartae is distinguished from congeners by the following: presence of small hooks on the first six to eight branched analfin rays of males, with two to four hooks on only the middle sections of the rays; adipose fin pigmented but with hyaline margins; an apophysis present on the dorsal margin of the rhinosphenoids that is directed toward the anterior tip; ventral process of the angulo-articular reduced and with a straight margin. Data on the phylogenetic position of the new species are presented.